2009
DOI: 10.1097/fbp.0b013e32832a8082
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant efficacy screening of novel targets in the chick anxiety-depression model

Abstract: The chick anxiety-depression model is a hybrid simulation, which may prove useful as an early preclinical dual pharmacological screen for novel therapeutics. Separate dose-response studies were conducted with seven test compounds that have screened positive for antidepressant effects in rodent depression models and included prasterone (5.0-40.0 mg/kg), memantine (2.5-20.0 mg/kg), ketamine (1.0-10.0 mg/kg), mifepristone (50.0-400.0 mg/kg), DOV216,303 (5.0-20.0 mg/kg), CGP36742 (2.5-15.0 mg/kg), and antalarmin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…A 20-min waiting interval for the drug to take effect was determined based on rat studies with m -CPP (Bilkei-Gorzó, Gyertyán & Lévay, 1998). Previous drug studies with young chicks have applied a 15-min waiting interval (Sufka et al, 2009; Hymel & Sufka, 2012) but there has been no previous application of m -CPP on adult hens. The same waiting interval was applied to birds injected with saline.…”
Section: Materials and Methods Experiments 2: Drug Dose Determinationmentioning
confidence: 99%
“…A 20-min waiting interval for the drug to take effect was determined based on rat studies with m -CPP (Bilkei-Gorzó, Gyertyán & Lévay, 1998). Previous drug studies with young chicks have applied a 15-min waiting interval (Sufka et al, 2009; Hymel & Sufka, 2012) but there has been no previous application of m -CPP on adult hens. The same waiting interval was applied to birds injected with saline.…”
Section: Materials and Methods Experiments 2: Drug Dose Determinationmentioning
confidence: 99%
“…For example, N-methyl D-aspartate (NMDA) receptor antagonist ketamine produces robust behavioral activation in adult zebrafish (Zakhary et al, 2011), strikingly paralleling the drug's hyperlocomotory effects in rodents (da Irifune et al, 1998). Although ketamine has anxiolytic-like action on clinical (Irwin and Iglewicz, 2010) and animal (Engin et al, 2009;Pietersen et al, 2006;Sufka et al, 2009) anxiety, anxiogenic effects were also reported in rodents (da . Therefore, this aspect of ketamine's behavioral pharmacology remains to be explored in zebrafish in detail.…”
Section: Other Systemsmentioning
confidence: 95%
“…However, there is considerable interest in using mifepristone to treat some forms of depression (see Benagiano et al, 2008b; Flores et al, 2006), stemming from the fact that it is also a glucocorticoid receptor antagonist (Attardi et al, 2004; Benagiano et al, 2008a). Recent studies have shown antidepressant-like effects of mifepristone in mice (Galeeva et al, 2007), rats (Korte et al, 1996; Wulsin et al, 2010), and chicks (Sufka et al, 2009). …”
Section: Discussionmentioning
confidence: 99%